Reduction of Airway Hyperresponsiveness by KWLL in Dermatophagoides-pteronyssinus-Challenged Mice. (4th March 2013) - Lin, Chih-Che; Wang, Shulhn-Der; Lin, Li-Jen; Hong, Hong-Jye; Wu, Chin-Jen; Chiang, Chung-Jen; Chao, Yun-Peng; Kao, Shung-Te
Abstract : Urine therapy has been commonly practiced in ancient civilizations including those of India, China, and Greece. The traditional Chinese medicine KWLL, the precipitation of human urine, has been used in China to alleviate the symptoms of asthma for thousands of years. However, the mechanism of action by which KWLL exerts its immunotherapy is unclear. This study attempted to elucidate the pharmacology of KWLL in mice that had been challenged recurrently by Dermatophagoides pteronyssinus (Der p). BALB/c mice were orally administered KWLL (1 g/kg) before an intratracheal (i.t.) challenge of Der p. Allergic airway inflammation and remodeling were provoked by repetitive Der p (50 μ g/mice) challenges six times at 1 wk intervals. Airway hypersensitivity, histological lung characteristics, and the expression profiles of cytokines and various genes were assessed. KWLL reduced Der p-induced airway hyperresponsiveness and inhibited eosinophil infiltration by downregulating the protein expression of IL-5 in bronchoalveolar lavage fluid (BALF). It also inhibited neutrophil recruitment by downregulating IL-17A in BALF. KWLL effectively diminished inflammatory cells, goblet cell hyperplasia, and mRNA expression of IL-6 and IL-17A in the lung. The reduction by KWLL of airway inflammatory and hyperresponsiveness in allergic asthmatic mice was mediated via immunomodulation of IL-5, IL-6, and IL-17A.